2008
DOI: 10.1121/1.2908289
|View full text |Cite
|
Sign up to set email alerts
|

Phonatory characteristics of excised pig, sheep, and cow larynges

Abstract: The purpose of this study was to examine the phonatory characteristics of pig, sheep, and cow excised larynges and to find out which of these animal species is the best model for human phonation. Excised pig, sheep, and cow larynges were prepared and mounted over a tapered tube on the excised bench that supplied pressurized, heated, and humidified air in a manner similar to that for excised canine models. Each excised larynx was subjected to a series of pressure-flow experiments with adduction as major control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 22 publications
(5 reference statements)
7
82
0
Order By: Relevance
“…This does not compare with the porcine glottis: Here, the CraF (topographically similar to the human vestibular fold, but presumably the main oscillator in porcine phonation [1]), displayed a vascular network wider than that of the CauF (topographically identical to the human vocal fold).…”
Section: Species-related Comparison Of the Microvascular Networkmentioning
confidence: 96%
“…This does not compare with the porcine glottis: Here, the CraF (topographically similar to the human vestibular fold, but presumably the main oscillator in porcine phonation [1]), displayed a vascular network wider than that of the CauF (topographically identical to the human vocal fold).…”
Section: Species-related Comparison Of the Microvascular Networkmentioning
confidence: 96%
“…However this remains a subject for debate as there is a further ventricle above the superior fold. It is suggested that vibration occurs at both folds as well as in the supraglottic structures during phonation (Kurita, Nagata et al 1983;Alipour and Jaiswal 2008).…”
Section: Porcine Modelsmentioning
confidence: 99%
“…By measuring amplitude, oscillation frequency, and phase difference of vocal fold vibration, it was concluded that canine and porcine larynges are the most appropriate models for vibratory or kinetic studies on phonation (Regner, Robitaille et al 2010). Alipour also studied vibratory characteristics of excised pig, cow and sheep larynges, and concluded that the porcine larynx had the highest range of phonation frequencies, making it a good candidate for animal studies (Alipour and Jaiswal 2008).…”
Section: Porcine Modelsmentioning
confidence: 99%
See 2 more Smart Citations